Preoperative and intraoperative ultrasound aids removal of migrating plant material causing iliopsoas myositis via ventral midline laparotomy: a study of 22 dogs. Issue 1 (December 2017) - Birettoni, Francesco; Caivano, Domenico; Rishniw, Mark; Moretti, Giulia; Porciello, Francesco; Giorgi, Maria; Crovace, Alberto; Bianchini, Erika; Bufalari, Antonello
Abstract Background Migrating plant material is often suspected clinically to be the underlying cause of iliopsoas myositis in the dog, but cannot always be found pre- or intraoperatively. In most cases, recurrence of clinical signs is related to failure to remove the plant material. Preoperative ultrasonography can be useful to visualize migrating plant material and to determine anatomical landmarks that can assist in planning a surgical approach. The purpose of the present study was to report the role of intraoperative (intra-abdominal) ultrasonography for visualizing and removing the plant material from iliopsoas abscesses using a ventral midline laparotomy approach. Results A retrospective case series of 22 dogs with iliopsoas muscle abnormalities and suspected plant material was reported. Preoperative visualization and subsequent retrieval of the plant material was performed during a single hospitalization. In all 22 dogs, the plant material (including complete grass awns, grass awn fragments and a bramble twig) was successfully removed via ventral midline laparotomy in which intraoperative ultrasonography was used to direct the grasping forceps tips to the foreign body and guide its removal. In 11 of these 22 dogs, the plant material was not completely removed during prior surgery performed by the referring veterinarians without pre- or intraoperative ultrasonography. Clinical signs resolved in all dogs and all dogs resumed normal activity after successful surgical removal of the plant material. Conclusion Intraoperative ultrasonography is a safe and readily available tool that improves success of surgical removal of plant material within the iliopsoas abscesses via ventral midline laparotomy. Moreover, ultrasonographic findings of unusual plant material can be useful in planning and guiding surgical removal, by providing information about the size and shape of the foreign body.